The role of rural grocery stores in refugee reception - Whyte, Z; Larsen, B; Schaldemose, M (Refugee Studies Centre, University of Oxford, 2018)
Our research with rural grocery store managers in Denmark suggests that the integration of asylum centres into the local social and economic life in rural areas is a key factor in successful refugee reception.